Smart Materials Meet Multifunctional Biomedical Devices: Current and Prospective Implications for Nanomedicine - Genchi, Giada Graziana; Marino, Attilio; Tapeinos, Christos; Ciofani, Gianni (Frontiers in Bioengineering and Biotechnology, 2017)
With the increasing advances in the fabrication and in monitoring approaches of nanotechnology devices, novel materials are being synthesized and tested for the interaction with biological environments. Among them, smart materials in particular provide versatile and dynamically tunable platforms for the investigation and manipulation of several biological activities with very low invasiveness in hardly accessible anatomical districts. In the following, we will briefly recall recent examples of nanotechnology-based materials that can be remotely activated and controlled through different sources of energy, such as electromagnetic fields or ultrasounds, for their relevance to both basic science investigations and translational nanomedicine. Moreover, we will introduce some examples of hybrid materials showing mutually beneficial components for the development of multifunctional devices, able to simultaneously perform duties like imaging, tissue targeting, drug delivery, and redox state control. Finally, we will highlight challenging perspectives for the development of theranostic agents (merging diagnostic and therapeutic functionalities), underlining open questions for these smart nanotechnology-based devices to be made readily available to the patients in need.